Numerical modeling of ballistic impact and penetration: computational aspects and challenges - Talebi, Hossein; Hamouda, Abdel Magid Salem (2005)
This paper presents a review on the knowledge which is necessary for ballistic modeling where the main objective is to develop a general view of Hydrocodes. The general view consist of formulation (Lagrangian vs. Eulerian ALE), time integration methods, material behaviour and damage modeling, contact, equation of state and mesh rezoning are discussed and the challenges are mentioned. Furthermore well established commercial software for pre and post processing and analysis (ANSYS, HYPERMESH, LS-DYNA and ABAQUS/Explicit) are introduced. Moreover a few examples of ballistic penetration into metallic targets are presented.